-5(a+2)+5=-7(5-a)-6

Simple and best practice solution for -5(a+2)+5=-7(5-a)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(a+2)+5=-7(5-a)-6 equation:


Simplifying
-5(a + 2) + 5 = -7(5 + -1a) + -6

Reorder the terms:
-5(2 + a) + 5 = -7(5 + -1a) + -6
(2 * -5 + a * -5) + 5 = -7(5 + -1a) + -6
(-10 + -5a) + 5 = -7(5 + -1a) + -6

Reorder the terms:
-10 + 5 + -5a = -7(5 + -1a) + -6

Combine like terms: -10 + 5 = -5
-5 + -5a = -7(5 + -1a) + -6
-5 + -5a = (5 * -7 + -1a * -7) + -6
-5 + -5a = (-35 + 7a) + -6

Reorder the terms:
-5 + -5a = -35 + -6 + 7a

Combine like terms: -35 + -6 = -41
-5 + -5a = -41 + 7a

Solving
-5 + -5a = -41 + 7a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7a' to each side of the equation.
-5 + -5a + -7a = -41 + 7a + -7a

Combine like terms: -5a + -7a = -12a
-5 + -12a = -41 + 7a + -7a

Combine like terms: 7a + -7a = 0
-5 + -12a = -41 + 0
-5 + -12a = -41

Add '5' to each side of the equation.
-5 + 5 + -12a = -41 + 5

Combine like terms: -5 + 5 = 0
0 + -12a = -41 + 5
-12a = -41 + 5

Combine like terms: -41 + 5 = -36
-12a = -36

Divide each side by '-12'.
a = 3

Simplifying
a = 3

See similar equations:

| 9(x)+8=90 | | 16=10-(-4x+2) | | 7v(z-2v)=12 | | 11-2g=3 | | -5X/6=-X-1/2 | | 20y+5=4+5y | | -6x+2(2x-15)=-6 | | -3(-2x+5)=17 | | -1.2=13x-18 | | 2y+12=66 | | z^2+14z=-45 | | X*240=12 | | 6=35 | | -6x-3(-3x+17)=-36 | | (5s+6)(s-2)= | | -7(4-4x)=-168 | | 8(t-2)+6t=7(2t+3)-9 | | -6(-7x-1)-x=-158 | | 7n-15=-16+8n | | -4x-6(-2x+15)=-10 | | 1/2(4/3)(3.14)(2.5)^3 | | -2x-3=2x+9 | | 4(6n-7)=140 | | 3(x-1)=7+5 | | n^2+9=34 | | Y=29(3)x | | 4(6n-7)=40 | | Y=29(3) | | 2/3x12/11 | | (n-6)(n-4)= | | 2j-12=2 | | -5.7=1.9+1.9z |

Equations solver categories